Lipid peroxides and atherosclerosis. Issue 6669 (4th February 1989) - Stringer, M. D.; Görög, P. G.; Freeman, A.; Kakkar, V. V.
Abstract : Plasma lipid peroxide concentrations were measured in 100 patients with occlusive arterial disease proved angiographically (50 patients with ischaemic heart disease, 50 with peripheral arterial disease) and compared with values in 75 control patients with no clinical evidence of atherosclerosis. Lipid peroxide concentrations were significantly higher in patients both with ischaemic heart disease (median 4.37 mumol/l (interquartile range 3.85-5.75 mumol/l); p less than 0.001) and with peripheral arterial disease (median 4.37 mumol/l (3.88-5.21 mumol/l); p less than 0.001) than in controls (median 3.65 mumol/l (interquartile range 3.29-3.89 mumol/l). Overall there was a significant but weak correlation between plasma lipid peroxide and plasma triglyceride concentrations (rs = 0.25; p less than 0.001) but not between plasma lipid peroxide and plasma total cholesterol concentrations. Furthermore, hypertension, obesity, diabetes, smoking, positive family history, and intake of beta blockers and thiazide diuretics were not associated with significant differences in lipid peroxide values. This study provides clinical support to experimental data indicating that peroxidised lipids may be important in atherogenesis and its complications and also suggests that peroxidised lipids may provide an index of the severity of atherosclerosis.